A method review of surgically induced hypertension in pregnant rats model: modified Reduced Uterine Perfusion Pressure (RUPP) - Zulkiflee, Khodijah; Mohd Zainudin, Maizura; Zainal Abidin, Fadhilah; Ismawi, Hidayatul Radziah; Yusoff Azmi Merican, Yusoff Sharizal (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2021)
Background: There are various animal models used in the study of pregnancy-associated hypertensive disorders. RUPP is one of the methods used to induce hypertension via surgical procedure by clipping both ovarian and uterine arteries with specified internal diameter of silver clip. In this study, we modified the method by using a surgical suture instead of clip.